Peningkatan Kemampuan Berbahasa Anak Usia 4-5 Tahun Menggunakan Media Video Animasi di Kelompok Bermain Sriwijaya Sadar Sriwijaya: Improving the Language Skills of Children Aged 4-5 Years Using Animation Video Media in the Sriwijaya Sadar Sriwijaya Playgrup - Lestari, Yuyun (Absorbent Mind, 2024)
The research aims to understand how educators use animation media to improve early childhood language skills and its impact during learning. The research method was carried out using classroom action research techniques at KOBER SRIWIJAYA in Bandar Sribhawono District. The research results showed that instructor training in utilizing animation media was not fully effective in Cycle I, so further action was needed in Cycle II. Cycle I got a score of 3.22 categorized as "Good", then in Cycle II there was an impressive improvement, especially getting a score of 3.66 with a classification of "very good". It is hoped that the animation media chosen as a medium to improve language skills will continue to develop. Based on Cycle I, the criteria score was 52.08% with the statement starting to develop (MB), so efforts are needed in Cycle II. In cycle II, the criteria score increased by 78.75% with the description of very well developed (BSB) and the criteria for using animation media to improve children's language skills were categorized as successful.